Konsep Dasar Metabolisme Tubuh, Metabolisme Karbohidrat, Protein, Lemak, Mineral, Elektrolit dan Vitamin - Ariangesty Safitri; Fatikha Aulya Rahma Marfuah; Resti Ayu Wahyuningsih; Safira Aurelia Wulandari; Sherli Olivia Khairatunisa; Silvia Nur Anggraini; Liss Dyah Dewi Arini (Indo Publishing, 2025)
Metabolism is a series of complex biochemical processes that occur within cells to maintain life. Metabolism encompasses two main stages: anabolism (molecule formation) and anabolism (molecule breakdown). Carbohydrates are the primary energy source, broken down into glucose through glycolysis and cellular respiration, which generates ATP for cellular activity. Proteins are also used as building blocks for tissue growth and repair, as well as enzymes and hormones, with amino acids produced from protein breakdown involved in the synthesis of essential molecules. Fats are a dense energy source and long-term energy reserve, and play a role in thermal insulation, cell membrane formation, and hormone production like estrogen. Minerals, such as calcium and iron, and electrolytes like sodium, potassium, and chloride, play crucial roles in maintaining electrolyte balance, osmotic regulation, nerve impulse transmission, and muscle contraction. Electrolyte imbalances can lead to disorders such as dehydration or cardiac arrhythmias. Meanwhile, vitamins—such as vitamin C (an antioxidant) and B-complex (a coenzyme)—support metabolic reactions, including energy synthesis and cell protection from oxidative damage. In general, the basic concept of metabolism emphasizes the importance of synergy between these nutrients to maintain body homeostasis. A proper balance of intake can prevent metabolic disorders, such as diabetes and malnutrition, and support optimal health.